Dual-Laser PBF-LB Processing of a High-Performance Maraging Tool Steel FeNiCoMoVTiAl - Gregor Graf (Materials, 2021)
As part of an international research project (HiPTSLAM), the development and holistic processing of high-performance tool steels for AM is a promising topic regarding the acceptance of the laser powder bed fusion (PBF-LB) technology for functionally optimized die, forming and cutting tools. In a previous work, the newly developed maraging tool steel FeNiCoMoVTiAl was qualified to be processed by laser powder bed fusion (PBF-LB) with a material density of more than 99.9% using a suitable parameter set. To exploit further optimization potential, the influence of dual-laser processing strategies on the material structure and the resulting mechanical properties was investigated. After an initial calibration procedure, the build data were modified so that both lasers could be aligned to the same scanning track with a defined offset. A variation of the laser-based post-heating parameters enabled specific in-situ modifications of the thermal gradients compared to standard single-laser scanning strategies, leading to corresponding property changes in the produced material structure. An increase in microhardness of up to 15% was thus obtained from 411 HV up to 471 HV. The results of the investigation can be used to derive cross-material optimization potential to produce functionally graded high-performance components on PBF-LB systems with synchronized multi-laser technology.